General woodworking - Groneman, Chris Harold, 1906- (New York : Webster Division, McGraw-Hill, 1982)
An industrial arts textbook which introduces the fundamentals of woodworking including the use of hand, machine, and portable power tools, finishing, upholstering, and wood technology.
Includes index.
Keywords: Woodwork (Manual training); Woodwork